Convalescent plasma does not provide adequate replacement of C1-Inhibitor and complements in COVID-19 patients. (28th October 2021) - Roth, Maxwell; Barouqa, Mohammad; Reyes, Morayma
Abstract: The rationale of Convalescent Plasma (CP) is to provide passive immunity to acutely ill COVID-19 patients. However, there are other pathologies of COVID disease that may be alleviated by CP. COVID-19 coagulopathy has been hypothesized to be a form of disseminated intravascular coagulopathy, a type of thrombotic microangiopathy. Complement activation has also been implicated in COVID-19 coagulopathy. An alternative hypothesis for additional benefits of CP is replacement of inhibitors of complements. C1-esterase inhibitor (C1-INH) is a major regulator of complement activation. We hypothesized that COVID-19 patients have decreased C1-INH and that CP transfusion would restore intravascular C1-INH and complement levels. We studied serial C1-INH and complement levels in COVID-19 patients before and after CP transfusion (200 mL) and their association with overall mortality. Methods: We identified COVID-19 patients (n=91) that received CP within the first 72 hours after admission. We collected serum and/or plasma samples at day prior and post-day 1, 3, and 10. C1 inhibitor, C3 and C4 were tested in these samples as well as in the respective CP unit given to each patient. Results: C1-INH levels day before transfusion were increased in COVID-19 patients (201.5% +/- 53%) in comparison to CP (93.2% +/- 26.2%). C1-INH transiently increased post CP transfusion and remained relatively high through day 10. No statistical difference was observed in C1-INH between survivors (n=53) and non-survivors (n=39) at any time point before or after transfusion. C3 was higher in COVID-19 patients in comparison to CP (161.5 +/-47.0 vs. 89.6 +/-15.3 mg/dL). However, C3 levels were significantly lower in non-survivors compared to survivors the day before transfusion (131.9 +/- 38.0 vs. 180.9 +/- 45.1 mg/dL, p=2.8E-06). Following transfusion, C3 levels decreased and remained steady afterwards; at all subsequent time points C3 levels were significantly lower in non-survivors compared to survivors (post-day 1: 130.6+/- 33.0 vs. 158.5 +/- 51.5 mg/dL, p=0.006; post-day 3: 116.6+/-46.5 vs. 146.2+/-42.8 mg/dL, p=0.01; post-day 10: 120.8+/-40.9 vs. 150.3+/- 45.9 mg/dL, p=0.03). C4 levels trended lower in non-survivors compared to survivors the day before transfusion (30.8+/- 15.3 vs. 37.9 +/- 16.7 mg/dL, p=0.08). The day following CP, there was a significant decrease in C4 across the entire cohort (35.1+/- 16.4 vs. 27.9+/- 18.3 mg/dL, p=0.01); subsequent levels remained steady. In conclusion, a single CP transfusion does not appear to restore C1-INH, C3 and C4 levels in hospitalized COVID-19 patients. CP transfusion is associated with a transient increase in C1-INH and decreasing C3 and C4 levels. Contrary to our hypothesis, C1-INH levels are increased in COVID-19 patients. The relationship between C1-INH and complements in COVID-19 remains to be fully elucidated. Prospective studies are needed to further delineate these relationships especially in the context of ongoing clinical trials of recombinant C1-INH in COVID-19 patients.